A novel approach for analyzing the effectiveness of the R&D capital for resource conservation: Comparative study on Germany and UK electricity sectors. (December 2020) - Khajehpour, Hossein; Miremadi, Iman; Saboohi, Yadollah; Tsatsaronis, George
Abstract: Limited access to energy resources and increasing demand for mitigation of the environmental impacts have necessitated higher production efficiencies. Therefore, the promotion of R&D activities has been one of the main parts of national energy policies. In this research work, two methods are used for assessing the effectiveness of the R&D capital on resource conservation. First, by developing the resource-included knowledge production function of the energy sector and second, through direct assessment of the functionality of resource productivity from R&D capital. Based on official data provided by national statistical centers, a comparative analysis has been conducted to examine the effectiveness of R&D in the electricity generation sectors in the United Kingdom and Germany. In these analyses, non-renewable exergy cost is used as an index of resource depletion and environmental burden. It is shown that, due to non-economic energy transition policies, the inclusion of the R&D investment does not result in statistically meaningful elasticity of production for the R&D capital. However, according to the second method, it is shown that the R&D investment in the United Kingdom has been more effective in resource conservation than in Germany. Possible reasons for such differences are discussed and recommendations for further investigations are presented. Highlights: The non-renewable exergy cost (NREC) is used as an index of resource depletion. Effectiveness of R&D capital for resource conservation in terms of NREC is studied. R&D capital and nonrenewable exergy cost are used as production factors. Knowledge production function is unsound for greening electricity sectors. R&D capital has been more effective for resource conservation in UK than Germany.